(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article focuses on the practical implementation of an art-pedagogical system in modern education. While the theoretical model of art pedagogy explains the developmental value of artistic activity, its real effectiveness depends on pedagogical conditions, institutional readiness and a gradual strategy of introduction. The article substantiates five key conditions: the development of teachers’ art-pedagogical competence, the creation of a psychologically safe creative environment, integration of art-based activity into curricula, the use of alternative assessment and cooperation between family, educational institution and community. The paper also describes four implementation stages: preparatory diagnostics, design, practical realization and monitoring-analysis. International experience, including integrated arts education and STEAM-oriented practices, is considered in relation to national cultural values and local educational needs. The results show that art-pedagogical implementation can increase motivation, communication, emotional intelligence and creative thinking if it is supported by systematic management and methodological guidance.